Studies in the Neotropical Apocynaceae L: The genus Allamanda in Colombia and a new combination - Morales, J Francisco (Phytotaxa, 2014)
A brief sypnosis of the genus Allamanda (Apocynaceae, Rauvolfoideae) in Colombia is given here, including a key and photographs of the species. A new combination, A. salicifolia is proposed.